Documenting the Rice Lexicon of the Dayak Ngaju Language: An Ethnolinguistic Study for Preserving Indigenous Knowledge and Cultural Heritage in Central Kalimantan - Siti Arnisyah; Holla Franciska; Yuherlita Marneci (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Background: The rice lexicon of the Dayak Ngaju language represents not only agricultural vocabulary but also indigenous ecological knowledge and cultural heritage that are increasingly vulnerable to language shift and changing agricultural practices. Despite its cultural significance, systematic documentation of rice-related lexical items in the Dayak Ngaju language remains limited. Aim: This study aims to document the rice lexicon of the Upper Katingan variety of the Dayak Ngaju language and to analyze the lexical and cultural meanings embedded in these lexical items through an ethnolinguistic approach. Method: Employing a descriptive qualitative design, the research was conducted in Tumbang Sanamang, Tumbang Jiga, and Tumbang Kanja villages, Katingan Regency, Central Kalimantan. Data were collected from six native speakers, including farmers, community leaders, and a Damang (customary leader), through semi-structured interviews, field observations, and documentation. The documented lexical items were transcribed using the International Phonetic Alphabet (IPA) and analyzed through ethnolinguistic interpretation supported by field evidence. The study documented nine rice-related lexical items: binyi, parei, kajugu, eta, apis, bunyer, bulu, behas, and kenta. Result and Discussions: The findings reveal that these lexical items form an interconnected lexical system representing the traditional rice cultivation cycle, from seed selection and cultivation to harvesting, post-harvest processing, and food preparation. Beyond their lexical meanings, the documented lexicons encode indigenous agricultural knowledge, sustainable resource management practices, ritual traditions, and culinary heritage that continue to shape the cultural identity of the Dayak Ngaju community. The integration of phonetic documentation, lexical analysis, and ethnolinguistic interpretation demonstrates that documenting culturally specific vocabulary contributes not only to regional language preservation but also to safeguarding indigenous knowledge and intangible cultural heritage. The findings provide valuable resources for language documentation, revitalization programs, cultural education, and future digital documentation of the Dayak Ngaju language.